2009
DOI: 10.1097/pts.0b013e318198dc8d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Contributions of an Electronic Web-based Reporting System

Abstract: This application effectively captured incidents, actions, and follow-up. Ease of data manipulation facilitated descriptive statistical analysis, and the ability to use branching algorithms may have helped in decision making about actions and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 17 publications
2
21
0
1
Order By: Relevance
“…While similar studies have reported difficulty in enrolling physicians, including surgeons, this study demonstrates that physicians were willing participate in proactive reporting systems. 37, 38 The fact that the web-based debriefing successfully solicited reports from nursing staff, physician extenders (e.g., physician assistants), technicians, physicians (e.g., anesthesiologists, surgeons), residents and students is suggestive that this active, web-based tool is successfully integrated into the workflow and fewer barriers for participation exist than the traditional incident reporting system.…”
Section: Discussionmentioning
confidence: 99%
“…While similar studies have reported difficulty in enrolling physicians, including surgeons, this study demonstrates that physicians were willing participate in proactive reporting systems. 37, 38 The fact that the web-based debriefing successfully solicited reports from nursing staff, physician extenders (e.g., physician assistants), technicians, physicians (e.g., anesthesiologists, surgeons), residents and students is suggestive that this active, web-based tool is successfully integrated into the workflow and fewer barriers for participation exist than the traditional incident reporting system.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers include time constraints, arduous forms, lack of understanding of the incident system, lack of feedback and action following incident reporting and others (Evans et al., ; Kingston et al., ; Schectman & Plews‐Ogan, ; Waring, ). Electronic reporting systems have been increasingly implemented in healthcare in order to counter these barriers with benefits, including accessibility, ease of use, viewing of reports, as well as a general increased efficiency of the feedback loop (Levtzion‐Korach et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated by recent studies, a well-designed, integrated and carefully implemented electronic reporting system can have several advantages including accessibility, increased accuracy, elimination of illegible forms, ease of use and automated reporting [15,18,28,58]. Use of electronic artefacts based on standard computerised spreadsheet formats, supported by well structured dropdown selection functions and self populating fields may reduce the report creation time at the sites, mitigate information storage issues and facilitate timely collection of data by the headquarters [26,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Most RACFs have paper forms to report medication incidents consisting of mostly narrative free text fields to document the details of the incident [25-27]. This information is then analysed to identify root causes and initiate corrective actions to address incidents [28]. …”
Section: Introductionmentioning
confidence: 99%